Financial and Safety Impact of Simulation-based Clinical Systems Testing on Pediatric Trauma Center Transitions. Issue 5 (26th September 2022) - Williams, Sacha A.; Fitzpatrick, Katie; Chandler, Nicole M.; Arnold, Jennifer L.; Snyder, Christopher W.
Abstract : Introduction: Simulation offers multiple tools that apply to medical settings, but little is known about the application of simulation to pediatric trauma workflow changes. Our institution recently underwent significant clinical changes in becoming an independent pediatric trauma center. We used a simulation-based clinical systems testing (SbCST) approach to manage change-associated risks. The purpose of this study was to describe our SbCST process, evaluate its impact on patient safety, and estimate financial costs and benefits. Methods: SbCST consisted of the following steps: (1) change-based needs assessment, in which stakeholders developed relevant simulation scenarios; (2) scenario implementation; and (3) postsimulation failure mode and effects analysis (FMEA) to identify latent safety threats (LSTs). LSTs were prioritized for mitigation based on the expected probability and severity of adverse event occurrences. We calculated the costs associated with the simulation process. We conservatively estimated SbCST cost savings using 3 approaches: (1) FMEA-based avoidance of adverse events; (2) avoidance of trauma readmissions; and (3) avoidance of medical liability lawsuits. Results: We implemented 2 simulation scenarios prechange. FMEA revealed 49 LSTs, of which 9 were highest priority (catastrophic severity and high likelihood of occurrence). These were prioritized and mitigated using the hospital's quality/safety framework. Cost-benefit analysis based on FMEA event avoidance demonstrated net cost savings to the institution ranging from $52, 000−227, 000 over the 3-month postchange period. Readmission-based and liability-based estimates also produced favorable results. Conclusions: The SbCST approach identified multiple high-impact safety risks and financially benefited the institution in managing significant pediatric trauma clinical process changes.